On the study of electrical conductivity of polycrystalline cadmium telluride - Nasar A.; Shamsuddin M. (My University, 2025)
The complex impedance of polycrystalline cadmium telluride has been measured as a function of frequency by a two-probe technique. The experimental data measured in the temperature range 301-565 K have been analyzed in the complex plane formalism and suitable equivalent circuits have been proposed in different temperature regions. The values of resistance and capacitance of bulk and grain boundary contributions have also been independently calculated from the Debye peak of spectroscopic plots. The role of bulk and grain boundary in the overall conduction process have been discussed with realistic justification.